Land-cover change and urban growth in the Mexico-Lerma-Cutzamala Hydrological Region, 1993–2018. (October 2022) - Manley, Ethan; Ogneva-Himmelberger, Yelena; Ruelle, Morgan; Hanumantha, Ravi; Mazari-Hiriart, Marisa; Downs, Timothy J.
Abstract: The Mexico-Lerma-Cutzamala Hydrological Region (MLCHR) encompasses all areas serving water needs of Mexico City Metropolitan Area and is home to 26.8 million people. Historically, this region has experienced extensive environmental and land cover changes due to urbanization, agricultural expansion, deforestation, growing population, floods and droughts. The main objectives of the study are to quantify the land cover changes and to identify spatial/temporal patterns of urban growth during 1993–2018. The results revealed that within the MLCHR over 25 years, urban land cover grew by 82% from its original extent in 1993. Shrubland and cropland contributed the most to the new urban land. The rate of change to urban has been increasing, from 38 km 2 /year in 1993–2004 to 53 km 2 /year in 2004–2018. Additionally, the spatial pattern of urbanization has become more dispersed over time, as new transitions to urban are happening farther away from existing urban land. This study is the first to quantify and locate urbanization within the entire hydrological region that serves the water and sanitation needs of the megalopolis. Its results will support future modeling efforts to understand the impacts of climate change on surface water bodies and aquifers within the MLCHR under different climate-change scenarios and to identify populations most vulnerable to projected water stress. Highlights: In the Mexico-Lerma-Cutzamala Hydrological Region urban land grew 82% over 25 years. Shrubland and cropland are major contributors to urban growth. Transitions to urban are happening further away from existing urban land. Results will be used in a dynamic water balance model under climate-change scenarios.